Enhancing Properties of Fiber Amplifier using Quantum Dots - De, Parnika; Singh, Shailendra (International Journal of Computer Sciences and Engineering, 2025)
In recent years, semiconductor nanocrystals quantum dots (QDs) have been extensively studied because of their unique optical and electronic properties compared to their bulk counterparts. This ability to tune the bandgap of the QDs through the control of the particle size can provide near-infrared emission covering the important wavelength region for the fiber optic communication. We have doped the optical fiber core by quantum dots (QDs) to integrate the emission characteristics of quantum dots with propagation characteristics of optical fiber. In particular, narrow bandgap materials such as PbS and PbSe have attracted much attention. Due to the large bulk exciton Bohr radii of PbS (18 nm), quantum confinement effect can be achieved over the wide range of the particle size. Application specific QDs can be incorporated into the optical fiber core. It was reported that PbS nanoparticles could provide the emission over the whole transmission window (1200–1700 nm) of silica fibers, and therefore could be promising for all-wave optical amplifiers. We have carried out numerical investigation such amplifier characteristics and have shown incremental gain values. Simulation results show that it is possible to design an optical amplifier with flattened gain characteristics over S, C, and L bands with low noise figure, moderate optical signal to noise ratio and minimum gain of 10 dB.